2016
DOI: 10.1175/jcli-d-16-0440.1
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Pacific SST Drivers of Recent Antarctic Sea Ice Trends

Abstract: A strengthening of the Amundsen Sea low from 1979 to 2013 has been shown to largely explain the observed increase in Antarctic sea ice concentration in the eastern Ross Sea and decrease in the Bellingshausen Sea. Here it is shown that while these changes are not generally seen in freely running coupled climate model simulations, they are reproduced in simulations of two independent coupled climate models: one constrained by observed sea surface temperature anomalies in the tropical Pacific and the other by obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 70 publications
6
84
1
Order By: Relevance
“…The results presented in this study leave open some important scientific questions, which deserve future investigation. Most importantly, the wind‐driven ocean dynamics identified in this study should work in concert with various other mechanisms identified in earlier studies, particularly wind‐driven sea‐ice transport [ Holland and Kwok , ] and cold and warm‐air advections linked to the IPO, AMO, and SAM [ Purich et al ., ; Meehl et al ., ; Clem and Renwick , ; Li et al ., ] and warming‐induced surface freshening [e.g., Bintanja et al ., ; de Lavergne et al ., ; Bintanja et al ., ; Zhang , ]. A more consistent and thorough mechanism will emerge when all the key factors and their interactions are considered together.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results presented in this study leave open some important scientific questions, which deserve future investigation. Most importantly, the wind‐driven ocean dynamics identified in this study should work in concert with various other mechanisms identified in earlier studies, particularly wind‐driven sea‐ice transport [ Holland and Kwok , ] and cold and warm‐air advections linked to the IPO, AMO, and SAM [ Purich et al ., ; Meehl et al ., ; Clem and Renwick , ; Li et al ., ] and warming‐induced surface freshening [e.g., Bintanja et al ., ; de Lavergne et al ., ; Bintanja et al ., ; Zhang , ]. A more consistent and thorough mechanism will emerge when all the key factors and their interactions are considered together.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Our analysis indicates that the increasing SH westerlies in the East Pacific sector and the poleward shifting SH westerlies in the Atlantic sector contributed to the seasonally and spatially inhomogeneous sea‐ice trends around West Antarctica during the past decades. These trends in the SH westerlies are known to be linked to ozone depletion and increasing greenhouse gases [e.g., Lee and Feldstein , ; Son et al ., ; Shindell and Schmidt , ; Gillett and Thompson , ], and the phase changes in the IPO and AMO [e.g., Lopez et al ., ; Meehl et al ., ; Purich et al ., ; Zhang et al ., ; Simpkins et al ., ; Lee et al ., ]. However, the trends in the SH westerlies could also emerge from the residuals of local and remotely forced atmospheric modes of variability from synoptic to interannual time scales, such as the SAM [e.g., Limpasuvan and Hartmann , ; Domingues et al ., ], the Pacific‐South American patterns [ Mo and Higgins , ; Lau et al ., ; Ghil and Mo , ], and ENSO‐forced extratropical Rossby waves.…”
Section: Interannual Variability Of West Antarctic Sea‐icementioning
confidence: 99%
See 1 more Smart Citation
“…This means that it is possible, although less likely, for an ice-free Arctic to occur earlier in a low emissions scenario than a high emissions scenario (Jahn, 2018). There is growing evidence that tropical decadal variability can influence sea-ice trends in both hemispheres (Ding et al, 2017(Ding et al, , 2019Meehl, Arblaster, et al, 2016;Meehl et al, 2018;Purich et al, 2016;Schneider & Deser, 2017). There is growing evidence that tropical decadal variability can influence sea-ice trends in both hemispheres (Ding et al, 2017(Ding et al, , 2019Meehl, Arblaster, et al, 2016;Meehl et al, 2018;Purich et al, 2016;Schneider & Deser, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On interseasonal to decadal time scales, climate variability in the tropics has been shown to strongly affect the Antarctic sea ice cover [e.g., Yuan , ; Turner , ; Stammerjohn et al , ; Ding et al , ; Simpkins et al , ; Li et al , ; Nuncio and Yuan , ; Meehl et al , ; Purich et al , ; Kohyama and Hartmann , ], thus creating the potential for short‐term changes to oppose long‐term climate trends. However, the relative importance of different tropical climate modes—such as the El Niño–Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD)—and the spatial details and seasonal modulation of the different teleconnection patterns are all still areas of active research and debate.…”
Section: Introductionmentioning
confidence: 99%